24. RESEARCH ON THE RESULTS OF EXTRACRANIAL CAROTID ARTERY STENOSIS TREATMENT BY INTERVENTION METHOD THROUGH CATHETER IN PATIENT OVER 60 YEARS OLD (Vietnam Journal of Community Medicine, 2024)
Introduction: With the advancement of the most interfering intervention devices, which is especially the introduction of the distance protecting device, carotid artery stenting is an effective method, leading to a gentle comfortable and safe procedure for elderly patients (more than 60 years old). Objective: To evaluate the results of extracranial carotid artery stenting.Methods: Intervention study, no control group, longitudinal follow-up.Results: Average patient age was 75.3 ± 4.2 years. Successful rate was 100%. After carotid artery stening: 6.4% of stroke and 2.1% of myocardial infartion. After 3 months of follow-up: 2.1% of stroke and 2.1% of myocardial infarction.Conclusion: Carotid artery stenting is a safe and effective treatment method for elderly patients (> 60 years old) with extracranial carotid artery stenosis.
Keywords: Carotid artery intervention, carotid artery stenosis, carotid artery stenting.